When is dependence on other organizations burdensome? The effect of asymmetric dependence on internet firm failure - Lee, Seung‐Hyun; Mun, Hee Jin; Park, Kyung Min (Strategic Management Journal, 2015)
Although critical resource providers offer ample access benefits to deficient firms, dependence on these resource providers is burdensome because dependency places deficient firms into a vulnerable position, especially when the dependency is asymmetric. Thus, we ask: I s it better to balance dependence among critical resource providers or asymmetrically depend on one if there is more than one resource provider? We use a unique context of the i nternet industry where satellite i nternet firms depend on portals that provide Web traffic and find that asymmetric dependence on portals increases the likelihood of failure, but market leaders suffer less from asymmetric dependence, while satellite i nternet firms with higher dependence on portals suffer more from asymmetric dependence . Copyright © 2014 John Wiley & Sons, Ltd.